Atención al cliente y su incidencia en las ventas en Romano Market Gourmet en la ciudad de Babahoyo periodo 2023. - Moreno Astudillo, Jessica Pilar (2024)
The present research paper aims to analyze the relationship between customer service and its impact on sales at Romano Market, a company dedicated to the marketing of mass consumption products. Customer service is a fundamental aspect for any business, as it directly influences customer satisfaction, loyalty and, therefore, the company's sales. In an increasingly competitive market, the quality of the service offered plays a crucial role in consumer loyalty. The research seeks to identify the main factors that affect the customer experience at Romano Market, such as friendliness, speed, effectiveness in problem solving and product knowledge by sales staff. In addition, it will explore how these elements contribute to increased sales, highlighting the importance of personalized service and efficient communication with customers. Through data collection, surveys and analysis of customer feedback, it is intended to provide a clear view of how customer service not only influences consumers' perception of the company, but also their purchasing decisions. The relationship between staff training and sales performance will also be evaluated, seeking strategies to improve the quality of service and, consequently, increase sales at Romano Market. This study aims to provide practical recommendations to optimize customer service and, thus, improve the company's commercial results.